Peranan Sanggar Seni Sighe Setangkai Dalam Pengembangan Seni Tari Daerah Empat Lawang - Rosa Antili; Efita Elvandari; Dedy Firmansyah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This research aims to determine and describe the role of the Sighe Setangkai Art Studio in the development of dance arts in the Empat Lawang area, especially traditional dance and creative dance in Empat Lawang Regency. This research uses a qualitative descriptive approach, while data collection is carried out using observation, interviews and documentation techniques. Data analysis in writing research results consists of three stages, namely: data reduction, data presentation, and conclusions. Checking the validity of the data using source triangulation techniques. The results of the research show that Sanggar Sighe Setangkai has a role in the development of dance in Empat Lawang Regency. The role of the Sighe Setangkai Studio in the development of dance in Empat Lawang Regency is carried out through studio activities related to dance production, training and performance activities. The role of Sanggar Sighe Setangkai in qualitative dance development can be seen from dance production activities. The role of Sanggar Sighe Setangkai in quantitative dance development can be seen from training activities and dance performances.